Potential of saccharomyces cerevisiae fermentation-derived postbiotic technology in mitigating multiple drug-resistant Salmonella enterica serovars in an in vitro broiler cecal model - Elena G. Olson; Dana K. Dittoe; W. Evan Chaney; Andrea M. Binnebose; Steven C. Ricke (PLoS ONE, 2025)
Diamond V Original XPC® is a Saccharomyces cerevisiae fermentation-derived postbiotic technology (SCFP) designed to interact synergistically with the animal to provide health benefits by enhancing immune function, supporting digestive integrity and absorption, and maintaining gastrointestinal (GIT) microbial balance in the host. The current study investigated the effects of 1.25% SCFP on multidrug-resistant (MDR) Salmonella serovars: S. Typhimurium (ATCC 14028), S. Enteritidis, S. Infantis, S. Heidelberg, S. Typhimurium DT104, and S. Reading, and shifts in cecal microbiota populations. Using an anaerobic in vitro poultry cecal model, cecal contents were inoculated with ~ 108 colony forming units (CFU) of MDR Salmonella serovars and incubated for 24 h at 37°C anaerobically. The treatments included: control group consisting of 0.2 g of crushed poultry feed, and a treatment group 0.25 g of feed +  1.25% inclusion of Original XPC® (SCFP). The SCFP significantly reduced five of the six serovars: S. Typhimurium ATCC, S. Enteritidis, S. Infantis, S. Heidelberg, and S. Reading (P <  0.05). Time significantly impacted S. Typhimurium DT104 reduction (P <  0.001). The most significant decrease was observed for S. Enteritidis (3.9 log10 CFU/mL), followed by S. Heidelberg (3.8 log10 CFU/mL), S. Infantis (3.4 log10 CFU/mL), S. Typhimurium ATCC (3 log10 CFU/mL), and S. Reading (1.8 log10 CFU/mL) compared to controls that averaged approximately 1 log10 CFU/mL reduction. Microbiota analysis at 24 h involved genomic DNA extraction, amplification using custom dual-indexed primers, and sequencing on the Illumina MiSeq platform. Sequencing data were analyzed using QIIME2-2021.11. S. Infantis and S. Heidelberg inoculated samples were the only groups that significantly enhanced microbial richness and evenness with SCFP addition at 24 h (P <  0.05). Pairwise comparisons revealed that samples inoculated with S. Reading and S. Typhimurium DT104 exhibited a minor change in microbial composition with SCFP, compared to other serovars that demonstrated increased microbial diversity with SCFP. Additionally, S. Infantis and S. Heidelberg inoculated samples exhibited phylogenetic diversity and microbial abundance with SCFP compared to controls at 24 h (P <  0.05). Lachnospiraceae CHKCI001 was significantly more abundant in SCFP-treated samples compared to controls (ANCOM, P <  0.05), suggesting SCFP impact on cecal fermenters and production of fermentation end products that may impact the ecosystem and inhibit pathogen growth. Although various serovars may exhibit somewhat different responses, SCFP effectively mitigated multiple MDR serovars of Salmonella under in vitro incubation conditions.